2020
DOI: 10.2174/0929867327666201005112231
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 related coagulopathy: what is known up to now

Abstract: : Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection has been a global challenge. The complicated forms of the Coronavirus Disease 2019 (COVID-19) can evolve to multiple-organ failure, including several coagulopathies related to a sudden worsening of respiratory status. This article aimed to review studies about hematological and hemostatic laboratory disorders directly related to COVID-19 and to discuss how SARS-CoV-2 causes these abnormalities. The coagulation cascade model is associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…To our knowledge, this is the first case of LAHPS with severe bleeding diathesis strongly associated with previous COVID-19 infection. This case adds to the complexity of COVID-19-related coagulopathy, which includes immune, endothelial, and coagulation systems, and calls attention to the possibility of bleeding complications, especially in patients using therapeutic anticoagulants ( 1 - 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first case of LAHPS with severe bleeding diathesis strongly associated with previous COVID-19 infection. This case adds to the complexity of COVID-19-related coagulopathy, which includes immune, endothelial, and coagulation systems, and calls attention to the possibility of bleeding complications, especially in patients using therapeutic anticoagulants ( 1 - 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most common coagulation abnormalities in COVID-19 patients are elevated D-dimer levels and fibrin split products ( 2 ). Other coagulation abnormalities, such as low fibrinogen levels, prolonged prothrombin time, and low platelet count, have also been reported ( 3 ). Despite all these derangements in coagulation tests, abnormal bleeding is uncommon.…”
mentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) first emerged in Wuhan, China, in December 2019 and subsequently spread globally [1]. Many articles have reported that it causes coagulation abnormalities and pulmonary thrombosis, contributing to poorer prognosis [2,3]. The prognosis of COVID-19 is improved by the use of anticoagulant agents during hospitalization [4].…”
Section: Introductionmentioning
confidence: 99%
“…For KEGG database the gene enrichment analysis on interactomes of NS7b, ORF1a, ORF3a and ORF8 showed pathway clusters highly significant and consistent with possible pathogenic mechanisms, such as the activation of the complement and of the coagulative cascade, (29) and the TGF-β-dominated immune response (30). In particular, the NS7b interactome revealed SNARE interactions in vesicular transport pathway, describing the mechanisms of intracellular vesicle trafficking and secretion, as the most significant pathway among all interactome (FDR< 0.…”
Section: Resultsmentioning
confidence: 93%